Impacts of plantation development on native customary rights (NCR) lands by SALCRA in Skibang, Bogag and Serasot, Sarawak - Ringgit, Dinggat (Universiti Malaysia Sarawak (UNIMAS), 2011)
(Successful rural development, of which land development was an important aspect, was extremely vital for the progress of rural communities in Sarawak, especially the Dayaks. This study revisited communities affected by land developed into oil plantations under a state development agency in the early 1990s. Participating native landowners from three largest villages in Jagoi area of Bau district were sampled to provide responses to a set of questions focused on various attributes of community development These included employment opportunities, improved income and higher standard of living, regular dividend payments, secured ownership of the NCR lands with official titles, opportunities for contract works in plantation related activities including transportation, supply and maintenance jobs, and spillover effects such as the establishment of formal and informal trading activities. The results indicated that there was no proper mechanism for the people in Serasot, Bogag and Skibang to participate meaningfully in the decision-making and managing of the oil palm schemes in their areas. It was clear that the experience of the participating landowners were very different from what were projected to them at the onset of the project development. A lot of the "promises" that were made had not been fulfilled. The participating communities were also somewhat disappointed, and they felt they had been misled to believe that their investments were sound. They were also concerned that government policies on land development were not fair for the native landowners. In their opinions, the state agency (implementing agency) had also failed to run the business efficiently and was thus unable to realize their stated objectives to provide job opportunities, good incomes and elevated standard of living, surveying and issuing out of land titles for NCR lands, protection of the environment, and delivery of the other related social benefits.